Holy water not so holy: Potential source of Elizabethkingia pneumonia and bacteremia in an immunocompromised host - Rahel T. Zewude; Matheus O. Bastos; May AlFalahi; Coleman M.F. Rotstein; Carson K.L. Lo (IDCases)
Elizabethkingia species are Gram-negative, glucose-non-fermenting bacilli predominantly found in soil and water, with Elizabethkingia anophelis increasingly recognized as a human pathogen. E. anophelis has also been reported in hospital outbreaks, suggesting the potential role of contaminated institutional water sources. Conventional microbiological methods often lead to misidentifying this pathogen for other members of the genus Elizabethkingia, suggesting a role for molecular methods for identification.We report a 67-year-old female who developed multiorgan failure requiring intensive care unit admission and mechanical ventilation while being treated with chemotherapy for Burkitt lymphoma. She developed pneumonia with Gram-negative bacilli isolated from her endotracheal aspirate culture, later identified as E. anophelis. She later developed bacteremia due to the same pathogen, which was confirmed by MALDI-TOF and whole genome sequencing. Waterborne transmission via holy water administration was postulated to be potential source of infection.Our case report highlights that E. anophelis may cause significant infection and should not be disregarded as contaminant, especially in immunosuppressed individuals. As a waterborne pathogen that may be brought into hospital environments, emphasis on educating family members, close nursing monitoring, and reporting of suspected, unsupervised manipulation of medical equipment should be undertaken to prevent contamination by this organism from outside sources.